SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN DOSEN BERBASIS WEB DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) (Studi Kasus Pada Instituto Profissional De Canossa Dili Timor Leste) - , Angelo da Costa; , Dra. Sri Hartati, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Permanent lecturers and part-time lecturers which dedicated is a benchmarks student success, then on the acceptance of new lecturers must be done assessment by analysis from the requirements of prospective lecturers, so assessment that does not impress subjective. Criteria set out in this case study is a formal education, work experience, age, and language. The purpose of this study is to make a decision support system for selecting candidates for permanent lecturers and part time lecturer with a web based at the Instituto Profissional de Canossa (IPDC) in Dili, Timor Leste. The results process selection of acceptance is done by ranking weights from the existing criteria using Simple Additive Weighting method (SAW). Decision Support System to process lecturer data based on criteria predetermined to produce ranking of lecturer in overall. System can also display rankings based on categories lecturers, namely the category of permanent lecturers and part time lecturer. The end result of this system is to display permanent lecturers be accepted and part time lecturer received under the order of ranking.